Arms Control as a Climate Mitigation Strategy: Examining the Nexus - Ahmad, Munir; Muhammad Karim; Zahid Hussain; Alyas Ali Chaichi (MultiTech Publisher, 2024)
Global ecosystems are seriously threatened by climate change, which calls for creative mitigation strategies. In an effort to fill a knowledge vacuum on the subject, this paper investigates the relationship between arms control and climate change mitigation. Specifically, it looks at how arms control policies may boost climate resilience. The research utilizes a thorough literature assessment, incorporating past viewpoints on arms control and current approaches to mitigating climate change. Approach-wise, a qualitative study is carried out to evaluate the empirical and theoretical relationship between weapons control policies and climate change mitigation. Important conclusions show that some weapons control programs can favorably impact climatic outcomes, offering a little-considered option for tackling environmental and security issues. The policy implications highlight the necessity of a more integrated approach to environmental governance and security, and the creation of focused, interdisciplinary policies is emphasized in the recommendations for future research. This study adds to the current conversation on mitigating climate change by providing a fresh viewpoint that supports the double advantages of successful arms control policies in promoting environmental sustainability on a worldwide scale.